g(-3)=0

Simple and best practice solution for g(-3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for g(-3)=0 equation:


Simplifying
g(-3) = 0

Reorder the terms for easier multiplication:
-3g = 0

Solving
-3g = 0

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Divide each side by '-3'.
g = 0

Simplifying
g = 0

See similar equations:

| -6x-3=5/7x-538/7 | | y=-3x+1.5 | | x+0.12x=1488 | | Log(x+1)16=8 | | -4x-3y=15fory | | 6+y=-6y | | 5x+5=-4x+5 | | 8x-(5x-5)=14 | | (7x+4)+85=180 | | (7x+4)+95=180 | | X=(2x-54) | | 9+2x=7x-16 | | A=a+(n-20)dforn | | 20+8(k+20)=-20-2k | | 15=-5X^2+20x-15 | | -15.43+4b=17.82+8.1b-4.96 | | -12.8z-8.1=-13.4z-19.08 | | 7(x+2)-x=5(x-2) | | 5+7lnx=4 | | x+.05x=700 | | -19.01+3.3p=5.6p+19.4 | | 7(x+2)-x=(x-2) | | (3x-6)2=2(2x-4) | | 7.85-2.8r=-3.3r | | A=a+(n-20)d | | 16a^9b+25a^4c^4= | | R(x)=x(23-.07x) | | 14.5s+19.93=10.3s-19.91-16.02 | | x+8.5=14.2 | | -12h=-11h-12 | | 3/4(x-5)+x=x | | 4m+15=6m-17 |

Equations solver categories